Improving lock-in thermography detection of microgaps located at the tooth-filling interface using a phase versus amplitude image signal extraction approach. (July 2017) - Streza, M.; Belean, B.; Hodisan, I.; Prejmerean, C.
Highlights: Adaptation of composites to the dental tissue is investigated by lock-in thermography. Gap signature enhancement through the second amplitude/phase images derivatives. Both scattering and absorption of light in teeth are taken into account. The phase image is more sensitive than the amplitude image for microgaps localization. Abstract: The aim of this study was to investigate the adhesion between some dental fillings and the dental hard tissue by two non-destructive techniques: lock-in thermography and optical microscopy. In this regard 10 non-carious human teeth were sealed with experimental and commercial sealants and then longitudinally sectioned in slices that were then examined. In the mean time some cavities were restored with some new dental fillings (giomers) and their sealing ability was analyzed by the two above mentioned techniques. Both amplitude and phase images obtained after lock-in detection procedure bear information on the presence of the gaps, carried out by small perturbations of amplitude or phase of propagating subsurface thermal waves. An image processing algorithm based on the Laplacian of the amplitude and phase images highlights the edges of the crack, leading to the localizations of cracks with a very good contrast. No difference between the adhesion capacity of sealants to dental enamel was observed. The phase image seems to be more appropriate for retrieval of micro-gaps than the amplitude image. Lock-in thermography technique together with the image processing procedure proved their capacity in evaluating dental interfaces.